The Molecular Scaffold Kinase Suppressor of Ras 1 (KSR1) Regulates Adipogenesis - Kortum, Robert L. (American Society for Microbiology, 2005)
Mitogen-activated protein kinase pathways are implicated in the regulation of cell differentiation, although their precise roles in many differentiation programs remain elusive. The Raf/MEK/extracellular signal-regulated kinase (ERK) kinase cascade has been proposed to both promote and inhibit adipogenesis. Here, we titrate expression of the molecular scaffold kinase suppressor of Ras 1 (KSR1) to regulate signaling through the Raf/MEK/ERK/p90 ribosomal S6 kinase (RSK) kinase cascade and show how it determines adipogenic potential. Deletion of KSR1 prevents adipogenesis in vitro, which can be rescued by introduction of low levels of KSR1. Appropriate levels of KSR1 coordinate ERK and RSK activation with C/EBPβ synthesis leading to the phosphorylation and stabilization of C/EBPβ at the precise moment it is required within the adipogenic program. Elevated levels of KSR1 expression, previously shown to enhance cell proliferation, promote high, sustained ERK activation that phosphorylates and inhibits peroxisome proliferator-activated receptor gamma, inhibiting adipogenesis. Titration of KSR1 expression reveals how a molecular scaffold can modulate the intensity and duration of signaling emanating from a single pathway to dictate cell fate.